Potential decarbonization for balancing local and non-local perishable food supply in megacities - Lin, Xintao; Qian, Jianping; Chen, Jian; Yu, Qiangyi; You, Liangzhi; Chen, Qian; Li, Jiali; Xiao, Pengnan; Jiang, Jingyi (Elsevier, 2025)
Ensuring urban food security while reducing carbon emissions from food systems is a key challenge. Food localization can reduce transport emissions; however, its role in agricultural production emissions reductions is unclear. Here, we explored the effects of localization of seven perishables, incorporating emissions from production and cold-chain logistics, in Beijing and Shanghai, China; determined decarbonization under different scenarios by increasing or decreasing the localization, with or without constrains, of each food category (balancing strategy). The results show that every 1% increase in the localization of vegetables, poultry, and aquatic products decreased 2020 emissions by 0.4–1.9 tCO2e, but for beef and lamb, it increased emissions by 0.2–2.9 tCO2e. Localization decreased cold-chain emission shares for all foods. The balancing strategy with constraints reduced emissions by 0.76 MtCO2e (5%) and 0.44 MtCO2e (2%) in 2020 in Beijing and Shanghai, respectively. Utilizing urban agriculture at all costs (i.e., without constraints) further reduced emissions by a factor of 3–4. Over 90% of Beijing’s emissions added by 2035 under the business-as-usual scenario were projected to be offset by the strategy. In Shanghai, the strategy could reduce emissions by an additional 0.44 MtCO2e. The results indicate that expanding imports of carbon-intensive ruminant meat to replace local production and reallocating urban resources to vegetables, poultry, and aquatic products could lead to more sustainable food supplies in megacities. Further development of cold-chain logistics is expected to reduce emissions in synergy with the balancing strategy. Our results could help inform better food system planning in megacities.